Analisis Pengelolaan Kecemasan dan Ketidakpastian Mahasiswa Asing Telkom University dalam Proses Adaptasi Budaya (Mahasiswa Asing Fakultas Komunikasi dan Bisnis Tahun Ajaran 2022/2023 Telkom University Prodi Ilmu Komunkasi) - Kaban, Riduan Maliek; Esfandari (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
International students who study in Indonesia are frequently experiencing anxiety in the process of adapting to the local culture. This is caused by various factors, such as differences in language, culture, values, and norms. This anxiety and uncertainty can hinder the adaptation process of foreign students when studying in Indonesia, especially Telkom University. This study aims to understand the mechanism of cultural adaptation and anxiety management carried out by Telkom University Foreign Students. The method used is a qualitative descriptive study using the constructivism paradigm. The data collection techniques used in this study were in-depth interviews, observation, and documentation. This study uses two units of analysis, namely the process of adaptation and management of anxiety and uncertainty. From the results of the research that has been done, the adaptation process experienced by each foreign student is different. The application of anxiety and uncertainty management in adapting is having a self-concept, having motivation to interact, reacting well, and building connections.